1995
DOI: 10.1136/oem.52.10.644
|View full text |Cite
|
Sign up to set email alerts
|

The risk of acquiring Q fever on farms: a seroepidemiological study.

Abstract: Objectives-To determine the occupational risk of Q fever. Design-Cohort study. Setting-Community: five English local authority districts. Subjects and methods-Prevalence and incidence of immunoglobulin G (IgG) specific antibody to Coxiella burnetii phase II antigen was measured in a representative (study) cohort of farm workers in the United Kingdom, and detailed exposure data were collected. Also seroprevalence of Q fever in a (control) cohort of police and emergency service personnel was measured.Results-Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 16 publications
(13 reference statements)
3
43
1
Order By: Relevance
“…It provides evidence that Q fever has not been endemic in sheep flocks in the mid-north of SA. Many serological surveys of occupational groups overseas have indicated that farmers have shown a proportion already positive for Q fever, 27% in English farmers [34] and 24% in sheep farmers in Sweden [35]. This outbreak supports the findings from Queensland that farmers are an important, often overlooked and harder to reach, occupational group at high risk of acquiring Q fever infection in Australia [15].…”
Section: Discussionsupporting
confidence: 77%
“…It provides evidence that Q fever has not been endemic in sheep flocks in the mid-north of SA. Many serological surveys of occupational groups overseas have indicated that farmers have shown a proportion already positive for Q fever, 27% in English farmers [34] and 24% in sheep farmers in Sweden [35]. This outbreak supports the findings from Queensland that farmers are an important, often overlooked and harder to reach, occupational group at high risk of acquiring Q fever infection in Australia [15].…”
Section: Discussionsupporting
confidence: 77%
“…This fin ding is con cor dant with the stu di es from Uni ted King dom and Spa in that fo und sig ni fi cantly hig her se rop re va len ce among tho se wor king in a farm en vi ron ment, working in ag ri cul tu re or ani mal hus bandry. 20 In our study the pre va len ce of C. bur ne ti i infec ti on was sig ni fi cantly hig her in men (63%) than wo men (37%), as ex pec ted. This is be ca u se, in this are a, mostly men are in vol ved in oc cu pa ti ons deman ding clo se con tact with li ves tock.…”
Section: Discussionsupporting
confidence: 62%
“…26 In a se ro e pi de mi o lo gi cal study compa ring study and con trol co horts from the UK, the pre va len ce of C. bur ne ti i pha se II an ti bo di es we re sig ni fi cantly hig her in the study co hort (27%) than the con trol co hort (11%). 20 Ge ne rally, stu di es in dica te that the Q fe ver pre va len ce is hig her in ru ral zo nes com pa red to ur ban zo nes, 14,20,22,[27][28][29] ho we ver the re are so me stu di es re por ting no sig ni fi cant corre la ti on bet we en se ro po si ti vity and the pla ce of resi den ce. 19,23 In our study, the samp les we re ob ta i ned mostly from ru ral zo nes.…”
Section: Discussionmentioning
confidence: 99%
“…C. burnetii differs from others rickettsia crucially in its resistance to physical conditions -such as extremes of temperature and desiccation. As a consequence, infection in an animal reservoir may result in wide dissemination of the organism in the environment [28,29]. Among exposed workers who reported using various personal protective equipment, all subjects reported never wearing a mask.…”
Section: Discussionmentioning
confidence: 99%